As maternidades na ficção científica - Bonato, Thays Eloize Leme (2022)
In this dissertation we present a comparative analysis between the science fiction works Brave New World (1932; 2014), The Left Hand of Darkness (1969; 1979) and The Handmaid’s Tale (1985; 2017), in order to analyze the different perspectives of maternity worked by these authors. There is also a look beyond motherhood, in the mother's own figure, her presence or absence in the narrative. We used scholars in the area of gender and motherhood such as BADINTER (1985, 1986, 2011), BEAUVOUIR (2014), FEDERECI (2017, 2019), FORNA (1999), KNIBIEHLER (2000), KITZINGER (1978) and SERRURIER (1993). There is also the presence of psycho analytic authors such as BENHAÏM (2007) and JUNG (2019). In addition to science fiction scholars who helped us understand the genre and its minutia such as BOOKER (1994), BLOOM (1987), CAUSO (2003), CLUTE (1995), ROBERTS (2000, 2018), SUVIN (1988, 2010) and TAVARES (1986). These authors acted as a driving force in our analysis, enabling a better understanding of the themes that we proposed to analyze. In this study, we carried out a comparative look between the maternity hospitals present in the afore mentioned novels, demonstrating the illustrated maternal plurality extracted from works of SF